Employment Dynamics in the Romanian Labor Market: A Markov Chain Monte Carlo Approach - Alexandru Voicu (Institute for the Study of Labor (IZA), 2002)
We use micro data from the Romanian Labor Force Survey to analyze the effect of the restructuring process on the employment dynamics of urban residents in the Romanian labor market. We analyze the way personal characteristics influence individuals? ability to adjust to labor market transformations. Sequential employment decisions made by individuals are modeled as Markov decision processes. The resulting multivariate probit models are estimated using Markov Chain Monte Carlo techniques.
Keywords: C15; J23; C35; 330; Employment dynamics; transition economy; Markov chain Monte Carlo; Arbeitsmarkt; Übergangswirtschaft; Erwerbsverlauf; Arbeitsangebot; Schätzung; Rumänien